Semi-rigid composite flange plate connections - Smitha, M. S.; Kumar, S. R. Satish (Journal of Structural Engineering, 2025)
Steel-concrete composite construction puts to best use the complementary structural properties of steel and reinforced concrete. However, adequate research has not been carried out on the seismic behaviour of composite beam to column connections and so they are often designed as pure steel connections neglecting the presence of the concrete slab. It has been realised that adequate composite action and the presence of additional concrete slab reinforcement across column lines can significantly enhance connection performance in steel-concrete composite frames. A composite flange plate connection with web cleats is studied here since it is expected to give adequate seismic performance at minimum cost. The results of the finite element analyses are presented and important parameters controlling the behaviour are identified. The effects of these parameters on the moment-rotation characteristics of the connection are discussed.